2008
DOI: 10.1021/ac800987m
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Calibration Strategy for in Situ Quantitative Monitoring of Phase Transition Processes in Suspensions Using FT-Raman Spectroscopy

Abstract: There is an increasing interest in using Raman spectroscopy to identify polymorphic forms and monitor phase changes in pharmaceutical products for quality control. Compared with other analytical techniques for the identification of polymorphs such as X-ray powder diffractometry and infrared spectroscopy, FT-Raman spectroscopy has the advantages of enabling fast, in situ, and nondestructive measurements of complex systems such as suspension samples. However, for suspension samples, Raman intensities depend on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 31 publications
0
35
0
1
Order By: Relevance
“…appeared to track the consumption and generation of each species effectively, they should be interpreted with caution since many factors could influence the Raman signal intensity. Many previous publications have demonstrated that particle size in a suspension could influence Raman signals via different mechanisms . For example, small particle size leads to larger surface area, thereby increasing the amount of material that can be effectively excited and leading to a stronger Raman signal.…”
Section: Discussionmentioning
confidence: 99%
“…appeared to track the consumption and generation of each species effectively, they should be interpreted with caution since many factors could influence the Raman signal intensity. Many previous publications have demonstrated that particle size in a suspension could influence Raman signals via different mechanisms . For example, small particle size leads to larger surface area, thereby increasing the amount of material that can be effectively excited and leading to a stronger Raman signal.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The minimal sample preparation required also makes this technique suitable for high-throughput analysis. Furthermore, the detail in Raman spectra provides information on the molecular properties and composition of the sample which can be used for identification and quality control purposes.…”
mentioning
confidence: 99%
“…Since SSD extracts quantitative information of the analyte of interest from SSD rather than variations in absolute spectral intensities, it has the potential to realize accurate quantification of particulate systems using Raman spectroscopy. SSD was applied to the monitoring of the anhydrate concentrations from in situ Fourier Transform (FT)‐Raman measurements made during the crystallization and phase transition processes of citric acid in water . It effectively mitigated the confounding effects of the overall solid content of the solid phase on Raman intensities and hence provided much more accurate in situ quantitative predictions of anhydrate concentration during crystallization and phase transition processes than traditional PLS calibration methods.…”
Section: Applications Of Ssd In Quantitative Analysis Of Complex Systemsmentioning
confidence: 99%